2015
DOI: 10.1120/jacmp.v16i6.5514
|View full text |Cite
|
Sign up to set email alerts
|

Dose differences in intensity‐modulated radiotherapy plans calculated with pencil beam and Monte Carlo for lung SBRT

Abstract: For patients with medically inoperable early‐stage non‐small cell lung cancer (NSCLC) treated with stereotactic body radiation therapy, early treatment plans were based on a simpler dose calculation algorithm, the pencil beam (PB) calculation. Because these patients had the longest treatment follow‐up, identifying dose differences between the PB calculated dose and Monte Carlo calculated dose is clinically important for understanding of treatment outcomes. Previous studies found significant dose differences be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…One of the planning factors is the algorithm used for dose calculation. Previous studies have shown that the use of PB dose results in an over‐estimation of the actual planned dose by approximately 10% . To evaluate the potential impact of tumour underdosing with PB calculation for local failure, we performed a matched‐pair study in which patients with and without local failure were paired and matched for other clinical factors in a population all treated with a dose of 50 Gy in five fractions using the same treatment planning and delivery technique.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the planning factors is the algorithm used for dose calculation. Previous studies have shown that the use of PB dose results in an over‐estimation of the actual planned dose by approximately 10% . To evaluate the potential impact of tumour underdosing with PB calculation for local failure, we performed a matched‐pair study in which patients with and without local failure were paired and matched for other clinical factors in a population all treated with a dose of 50 Gy in five fractions using the same treatment planning and delivery technique.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the use of PB dose results in an over-estimation of the actual planned dose by approximately 10%. [9][10][11][12][13][14][15] To evaluate the potential impact of tumour underdosing with PB calculation for local failure, we performed a matched-pair study in which patients with and without local failure were paired and matched for other clinical factors in a population all treated with a dose of 50 Gy in five fractions using the same treatment planning and delivery technique. Cases of local failure were successfully matched to control subjects while accounting for similar lengths of follow-up time and similar clinical features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both studies suggest that the dose‐calculation algorithm should be transitioned from TMR10 to convolution. Prior to this transition, however, the accuracy of the convolution algorithm of the LGP should be verified although the convolution algorithm has been extensively employed and verified in external beam radiotherapies . In this study, we assessed the accuracy of the absolute dose distributions that were obtained with the convolution algorithm of the LGP version 10.1.…”
Section: Introductionmentioning
confidence: 99%